1968
DOI: 10.1002/cne.901330107
|View full text |Cite
|
Sign up to set email alerts
|

The aorticorenal ganglion and its role in renal innervation

Abstract: A detailed dissection of the renal plexus and the aorticorenal area was carried out in 57 adult cadavers (32 males and 25 females). This study showed that the aorticorenal ganglia may be located anywhere in the general area of the junction of the renal arteries with the aorta. These ganglia were found to be partly fused with the celiac ganglion in 4% on the right side and in 12% on the left. All three thoracic splanchnic nerves (greater, lesser, and least) may have rami which terminate in the sorticorenal gang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
27
0

Year Published

1969
1969
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 11 publications
8
27
0
Order By: Relevance
“…In this regard, Pokushalov et al found that high‐frequency ES delivered at the ostium of the targeted RA at a frequency of 20 Hz, with an amplitude of 15 V and pulse duration of 10 ms, caused a sudden increase of BP by a mean of 30 mm Hg. These physiological findings are consistent with the anatomical findings of Mizeres and Norvell, demonstrating the presence of the ARG. A recent report also confirmed the presence of the ARGs and a higher sympathetic nerve density at the junction of the aorta and RAs .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this regard, Pokushalov et al found that high‐frequency ES delivered at the ostium of the targeted RA at a frequency of 20 Hz, with an amplitude of 15 V and pulse duration of 10 ms, caused a sudden increase of BP by a mean of 30 mm Hg. These physiological findings are consistent with the anatomical findings of Mizeres and Norvell, demonstrating the presence of the ARG. A recent report also confirmed the presence of the ARGs and a higher sympathetic nerve density at the junction of the aorta and RAs .…”
Section: Discussionsupporting
confidence: 91%
“…[1][2][3][4]19 It should be noted that the autonomic anatomy of the renal nerves shows important differences between dog and man. In the elegant studies of Mizeres on the anatomy of the autonomic nervous system in dog, 8 Norvell 20 found that, in a study of 57 adult human cadavers, the ARG is located in or around the ostia of the RAs and aorta. It is of interest that stimulation of the ARG and at the RA adventitia with the same ES parameters induced a much greater mean hypertensive effect at the former (207 ± 44/147 ± 26 mm Hg) than at the latter (157 ± 26/114 ± 18 mm Hg).…”
Section: Es Delivered To the Ras And Argmentioning
confidence: 99%
“…Shvalev (1 1) also observed the consistent localization of ganglia subcapsularly in the canine kidney. The preganglionic fibers, which course through the renal plexus, are probably thoracolumbar in origin ( 16). The possibility of a craniosacral contribution was considered by Shvalev, who also allowed for the possibility of free-lying intramural ganglion cells.…”
mentioning
confidence: 99%
“…Although atropine action at the ganglionic level is not ordinarily accepted, this seems possible at the dosage given by the intraarterial route (1 5 ) . The probable sites would be the aorticorenal ganglia, which supply postganglionic adrenergic constrictor fibers to the kidney vasculature via the renal plexus (16). The transient fall in blood pressure during atropine infusion indicated that this was probably a rather widespread systemic effect , affecting other sympathetic, preganglionic fibers, innervating arterioles of the systemic vasculature with adrenergic postganglionic vasoconstrictur fibers, An added possibility is that atropine, in the dosage given, depressed the function of the neurons of the vasoconstrictor centers of the medulla (17).…”
mentioning
confidence: 99%
“…Knowledge regarding the intrinsic innervation of the kidney was based for years on experiments using various standard nervestaining techniques, particularly silver impregnation and methylene blue (1)(2)(3)(4). Recently, there have been several reports on the application of newer histochemical methods to the study of renal innervation.…”
mentioning
confidence: 99%